2017
DOI: 10.3390/su9061060
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Impacts of Environmental Factors on the Cycling Behavior of Bicycle-Sharing Users

Abstract: Abstract:As it is widely accepted, cycling tends to produce health benefits and reduce air pollution. Policymakers encourage people to use bikes by improving cycling facilities as well as developing bicycle-sharing systems (BSS). It is increasingly interesting to investigate how environmental factors influence the cycling behavior of users of bicycle-sharing systems, as users of bicycle-sharing systems tend to be different from regular cyclists. Although earlier studies have examined effects of safety and conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 44 publications
(60 reference statements)
1
37
0
1
Order By: Relevance
“…In most urban transportation systems, there is a growing interest to increase the attractiveness of cycling [1,3]. E-bikes are electric-assist bicycles which can travel longer distances, provide higher mobility, and reduce barriers to users compared to conventional bicycles.…”
Section: Introductionmentioning
confidence: 99%
“…In most urban transportation systems, there is a growing interest to increase the attractiveness of cycling [1,3]. E-bikes are electric-assist bicycles which can travel longer distances, provide higher mobility, and reduce barriers to users compared to conventional bicycles.…”
Section: Introductionmentioning
confidence: 99%
“…It could be important for the City of Tshwane to improve cycling safety so as to promote cycling as a sustainable mode of transport. Cycling initiatives that improve safety of cycling tend to increase cycling among the public [27].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also found that suffering from a lack of ancillary, urban cycling facilities significantly impacts the usage of bicycles, and in addition, the interminable sign-up process and mandatory helmet legislation lessen the spontaneity of cycling [11]. A study by Sun et al claimed that traffic accidents and congestion, public transit accessibility and violent crime would influence the usage of public bike-sharing services [24]. With regard to the new-generation of DBSPs, Shen et al investigated bicycle usage in Singapore.…”
Section: Influencing Factors and Stakeholders Related To The Sustainamentioning
confidence: 99%